Sai o consumidor, entra o cidadão: educação como práticas da liberdade no curso de bacharelado em direito da Universidade Federal do Oeste do Pará. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Faced with a lot of legal courses offered in the country and an instrumental legal formation the present dissertation had as scope to analyze the problem of legal education of law courses in Brazil, as well as to investigate the form that the legal education developed by the Bachelor in Law of the Federal University of Western Pará (UFOPA) has contributed to the construction of an emancipatory education. For that, the following objectives were formulated: i) to define the theoretical bases and the fundamental subjects for the discussion of an emancipatory legal education; Ii) to investigate the legal education offered in the UFOPA Law Degree, through the analysis of the Pedagogical Project of the Bachelor of Laws (PPC - Pedagogical Project of the Course), questionnaires to the students of the classes 2012, 2013, 2014 and 2015, questionnaires to teachers and interview to the coordinator; Iii) to analyze the legal framework and the context of creation of this new university, examining the Plan of Restructuring and Expansion of the Federal Universities (Reuni); Iv) identify existing and potential emancipatory practices in the UFOPA Law Degree. The research had a qualitative character and for the objectives the methodological proposal was exploratory and descriptive, how technical procedures we use bibliographical research, documentary research and empirical research. The theoretical method adopted was dialectical historical materialism, that is, a non-dogmatic analysis was made and based on the material reality of the object of research, in relation to its historical development. The main authors of the theoretical foundation were Boaventura de Sousa Santos, Paulo Freire and István Mészáros. In the interpretation of the collected data, we rely on the Content Analysis of Laurence Bardin (2011) and the Triangulation Technique (MARCONDES; BRISOLA, 2014). The results of the bibliographic research have shown that legal courses in Brazil have developed a dogmatic legal education, positivist and uncritical, focused on the labor market and little concerned with the possibilities of changes in social relations. Such macro context reverberates in UFOPA. However, even if the tonic of creation and expansion of legal courses follows the market logic and is sometimes distanced from the social problems with which the future bachelors will deal daily, there are spaces for the construction of emancipatory practices. These spaces already exist in UFOPA and in other institutions, producing more dialogic knowledge that makes it possible to rethink against hegemonic within the academy. They are spaces of ecologies of knowledge, which share knowledge close to those worked by the epistemologies of the South and by decolonial/uncolonial thinking. The conclusion is that these practices still need to be advanced in order to have greater participation of academics and have more legitimacy as hegemonic proposals for the teaching, research and extension of law courses in Brazil.
Keywords: Educação; Práticas da liberdade; Bacharelado em Direito; UFOPA; Emancipação.; CNPQ::CIÊNCIAS HUMANAS; HISTÓRIA, POLÍTICA E GESTÃO EDUCACIONAL NA AMAZÔNIA